(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Kabul city capital of Afghanistan this city is suffering from a highly congested traffic, caused by a dramatic increase of its population and air pollution.this research is very important for the green sustainable transportation system for Kabul city because transport is a major user of energy and burn most of oil that causes to release nitrous oxides, carbon dioxides and particulates. When we want to take step toward green transportation system and should be pay attention the consumption of its fuel in the internal combustion engine. And also decrease the contamination of harmful material to the environment. Because transportation system is one of the vast contribution to the global warming and also recommended those who to drive old cars in the large populated urban city and prevent them from driving old cars in the urban city. The existence transportation system and the crowded urban city that particulate large quantity of carbon monoxide, carbon dioxides, nitrous oxides, methane and other harmful material to the environment. Which is dangerous for the existence ecosystem of world.the clean environment for the existence of ecosystem is very essential because that impair the growth of ecosystem. And also struggle to create attractive environment for the existence and development of ecosystem. Thus, to rebuild green and sustainable environment for the ecosystem. And should undertake to handle that tools and machines to particulate vast amount of harmful material into the atmosphere.and to rebuilt clean, green, safe, affordable, accessible, secure and less harmful transport for the city.